104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
1987 Fresno County Bar Association President thanking everyone for their Fresno County Bar Association Board service and introducing evening entertainment TorNino's sign on lectern